2006
DOI: 10.1152/ajpendo.00038.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that endogenous SST inhibits ACTH and ghrelin expression by independent pathways

Abstract: Corticosterone and total ghrelin levels are increased in somatostatin (SST) knockout mice (Sst Ϫ/Ϫ ) compared with SST-intact controls (Sst ϩ/ϩ ). Because exogenous ghrelin can increase glucocorticoids, the question arises whether elevated levels of ghrelin contribute to elevated corticosterone levels in Sst Ϫ/Ϫ mice. We report that Sst Ϫ/Ϫ mice had elevated mRNA levels for pituitary proopiomelanocortin (POMC), the precursor of adrenocorticotropic hormone (ACTH), whereas mRNA levels for hypothalamic corticotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 50 publications
14
86
2
1
Order By: Relevance
“…We have previously reported that fasting up-regulates the expression of native ghrelin in the mouse PIT, but has no effect on HPT mRNA levels (Luque et al 2006b(Luque et al , 2007. Consistent with these findings, in the current report, we observed that the expression of both native ghrelin (Fig.…”
Section: Metabolic Regulation Of the In2-ghrelin Variantsupporting
confidence: 92%
See 4 more Smart Citations
“…We have previously reported that fasting up-regulates the expression of native ghrelin in the mouse PIT, but has no effect on HPT mRNA levels (Luque et al 2006b(Luque et al , 2007. Consistent with these findings, in the current report, we observed that the expression of both native ghrelin (Fig.…”
Section: Metabolic Regulation Of the In2-ghrelin Variantsupporting
confidence: 92%
“…This cell line was maintained in our laboratory according to previously described methods (Belsham et al 2004). Primary PIT cell cultures were prepared by enzymatic dispersion of 3-4 pituitaries/experiment from 8-to 10-week-old male mice, as previously described by our laboratory (Luque & Kineman 2006, Luque et al 2006b). …”
Section: Effect Of Fasting On In2-ghrelin Expressionmentioning
confidence: 99%
See 3 more Smart Citations